Living on the Own Island? Aligned Collaboration Between Family Physicians, Nurses, Dieticians, and Patients With Diabetes Type 2 in an Outpatient Care Setting in Northern Italy: Findings From a Qualitative Study - Heike Wieser MSc; Giuliano Piccoliori MD; Marianne Siller RN, MSc; Evi Comploj MD, Priv.-Doz., FEBU, FEAPU; Harald Stummer Prof. Dr., MMag (SAGE Publishing, 2020)
Introduction: Diabetes mellitus type 2 (DM2), one of the four most important chronic diseases worldwide, is generally considered to be preventable. However, it is not yet sufficiently clear whether an aligned collaboration between different health professions could facilitate behavioral changes to be made by patients with DM2 regarding their eating and physical activity habits. Objective: To explore if and how far in current outpatient care for 3 health-care professions it is an objective to collaborate with each other supporting patients with DM2 in changing their eating and physical activity habits. Methods: We conducted 18 qualitative problem centered interviews with selected family physicians, nurses, dieticians working in outpatient setting and patients with DM2, transcribed verbatim, and analyzed with qualitative content analysis. Results: Issues identified ranged from description and reflection of current health-care practice, strategies, and hindrances to cope with changes of eating and physical activity behaviors as well as for health-care practice regarding interprofessional collaboration and patient-centered care up to considerations about collaboration and patient centricity (for health professionals and patients to achieve goals) and changes and ideas of "ideal care practice". Discussion: The included professional groups work predominantly for themselves. Collaboration currently only takes place when individually triggered and neither structured nor organized.